Demystifying the mist: Sources of microbial bioload in dental aerosols. Issue 9 (27th July 2020) - Kumar, Purnima S.; Subramanian, Kumar
Abstract: The risk of transmitting airborne pathogens is an important consideration in dentistry and has acquired special significance in the context of recent respiratory disease epidemics. The purpose of this review, therefore, is to examine (1) what is currently known regarding the physics of aerosol creation, (2) the types of environmental contaminants generated by dental procedures, (3) the nature, quantity, and sources of microbiota in these contaminants and (4) the risk of disease transmission from patients to dental healthcare workers. Most dental procedures that use ultrasonics, handpieces, air‐water syringes, and lasers generate sprays, a fraction of which are aerosolized. The vast heterogeneity in the types of airborne samples collected (spatter, settled aerosol, or harvested air), the presence and type of at‐source aerosol reduction methods (high‐volume evacuators, low volume suction, or none), the methods of microbial sampling (petri dishes with solid media, filter paper discs, air harvesters, and liquid transport media) and assessment of microbial bioload (growth conditions, time of growth, specificity of microbial characterization) are barriers to drawing robust conclusions. For example, although several studies have reported the presence of microorganisms in aerosols generated by ultrasonic scalers and high‐speed turbines, the specific types of organisms or their source is not as well studied. This paucity of data does not allow for definitive conclusions to be drawn regarding saliva as a major source of airborne microorganisms during aerosol generating dental procedures. Well‐controlled, large‐scale, multi center studies using atraumatic air harvesters, open‐ended methods for microbial characterization and integrated data modeling are urgently needed to characterize the microbial constituents of aerosols created during dental procedures and to estimate time and extent of spread of these infectious agents.